Factors affecting the use of herbal medicines for weight loss in overweight and obese adolescents - Yim, Mi Hong; Lee, Boram (Frontiers in Pediatrics, 2023)
Objectives: Herbal medicine (HM) is widely used to treat obesity in adolescents worldwide since the currently available interventions have low compliance and lack long-term effects and safety data. This study aimed to analyze the factors affecting HM use for weight loss in overweight and obese adolescents. Methods: A total of 46,336 adolescents were included in this cross-sectional study based on the Korea Youth Risk Behavior Web-Based Survey. Three models of HM use for weigh loss were developed by sequentially adding predisposing, enabling, and need factors according to Andersen’s model using multiple logistic regression analyses considering the complex sampling design. Results: Male and female high school students and students from low perceived household economic status were less likely to use HM for weight loss. Students whose fathers had a college degree or higher, depressed mood, and two or more chronic allergic diseases were more likely to use HM. Male students who perceived their body image as fat or very fat tended to use HM less than those who perceived their body image as very thin, thin, or moderate. Obese female students tended to use HM more than overweight female students. Conclusion: These results can be used as the bases to promote HM use, provide ideas for future research, and strengthen the health insurance coverage extension for weight loss interventions.